The Correlation between Retinal Nerve Fibre Layer Thickness, Optic Nerve Head Parameter, and Related Risk Factor in Glaucoma Patient: Oral Presentation - Observational Study - Resident - Wardhana, Arif Kusuma; Ekantini, Retno; Gani, Tatang Talka; Jati , Krisna Dwi Purnomo (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesTo investigate the correlation between retinal nerve fibre layer (RNFL) thickness and the past RNFLthickness, related risk factor (gender, age, myopia, intraocular pressure (IOP), blood pressure). AndRNFL parameter (symmetricity and four quadrants RNFL thickness) and optic nerve head parameter(rim area and vertical cup disc ratio) Methods39 right eyes of both sex and various age underwent examination including IOP measurement,subjective refraction for determining refractive error, and optical coherence tomography (OCT) forRNFL and ONH analysis. The follow up were done after one year. ResultsThe RNFL symmetricity, superior, nasal, inferior, temporal RNFL thickness showed significancecorrelation with RNFL thickness (R= 0.487, p= 0.002), (R= 0.915, R= 0.749, R= 0.897, R= 0.702with p= <0.001), but not showed significance correlation with rim area and vertical cup disc ratio(R= 0.175, p= 0.286) and (R= -0.093, p= 0.574). A significance correlation also showed withincreasing age, gender, and systolic blood pressure (R= -0.387, p= 0.015), (R= 0.441, p= 0.005) and(R= -0.418, p= 0.008). But not showed significance correlation with history of past RNFL thickness,refractive error, IOP, and diastolic blood pressure (R= 0.258, p= 0.113), (R= 0.005, p= 0.975), (R=-0.234, p=0.152), and (R= 0.060, p=0.717). ConclusionRNFL thickness measurements showed significance correlation with RNFL parameter. It is not clearif past RNFL thickness, refractive error and IOP related with RNFL thickness even showedsignificance correlation with age, gender, and systolic blood pressure.